Pelatihan Aplikasi Perpustakaan Berbasis Web Pada Sekolah Budi Satrya - Marwan Elhanafi, Andi; Ruswan Nurmadi; Annisa Ashari; Fahrika Ariyani Lubis; Muhammad Azhari; M. Dahrul Rizki; Dedy Irwan (Jurnal Pengabdian Masyarakat, 2023)
Web-based library application training at Budi Satrya School is a solution designed to improve the efficiency and accessibility of library services. The purpose of this application training is to make it easier for students and library staff to find, borrow, and return books. Training The app also describes administrative features that allow library staff to manage book collections, student data, and borrowing more efficiently. In this application training, various important menus have been explained such as book search, admin management, student data management, book information management, and website display settings. These menus ensure users can easily access and use the features provided. With this web-based library application training, it is hoped that the library staff of Budi Satrya School can improve skills in library management, improve the better experience for library staff and improve the management of book collections. Evaluation needs to be done to ensure the sustainability and improvement of the quality of services carried out by library staff in managing this application. Keywords: Library, Website, Library Application, Budi Satrya School